EKSISTENSI PESANTREN DAN KONTRIBUSINYA DALAM PENDIDIKAN KARAKTER - Hamruni Hamruni; Ricky Satria W. (Jurnal Pendidikan Agama Islam, 2016)
Historically, boarding schools (pesantren) since its inception has never silent in face of religious social problems. Activities pesantren in response to global problems has been demonstrated since the early days of glory. Involvement of schools in globalized world has been proved by historical facts are not possible to be denied. Pesantren with various elements of education has been able to develop character education to be maximal. This is reflected in planting of theoretical value obtained from studies book in form of real practices in daily life. Habit can form a good character to students, and process naturally without forced. Success of schools in shaping character invites many other institutions to emulate design of schools, ie educational boarding. Many education experts believe that concept of a boarding education such as that implemented by schools actually capable of shaping students’ character.